The Influence of J.A. Comenius’ Ideology on the Development of Slovak Pedagogy - Cabanova, Vlasta (Biuletyn Historii Wychowania, 2023)
Pedagogical opinions of J. A. Comenius and his unique reflections on the improvement of the society represent one of the main standpoints for the development of humanist pedagogy around the world. His concept of education as well as his ideas on how to resolve many of the world’s complex problems were at the time highly progressive and have influenced the society’s way of thinking in Slovakia as well. The credit for the popularisation of his ideas goes to many notable personalities in Slovakia in the 19th and 20th centuries. His ideas are still tangible in the process of contemporary teaching of pedagogues, from primary schools all the way to universities.